2004
DOI: 10.1007/s00431-004-1473-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surfactant function at birth determined by the stable microbubble test in term and near term infants with respiratory distress

Abstract: the results suggest that deficiency or dysfunction of the surfactant system is involved in the majority of cases of respiratory distress in near term and possibly term babies. The stable microbubble test can enable clinicians to take an earlier decision to give surfactant to term or near term infants with more severe and progressive respiratory distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
(24 reference statements)
2
9
0
Order By: Relevance
“…All the staff of the unit is trained in the technique as SMT has been routinely used for many years. The good inter-and intra-observer agreement in the SMT performed in gastric aspirates has already been reported [19] .…”
Section: Methodsmentioning
confidence: 82%
“…All the staff of the unit is trained in the technique as SMT has been routinely used for many years. The good inter-and intra-observer agreement in the SMT performed in gastric aspirates has already been reported [19] .…”
Section: Methodsmentioning
confidence: 82%
“…We found some intra-observer variability which may be due to the sample being frozen for a month and then re-analysed. However, the effect of freezing on gastric aspirates has been tested by Fiori et al [20] and found not to significantly influence results. We did not assess inter-observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess inter-observer variability. Fiori et al [20] found a κ coefficient of 0.88 for counts by different observers at a higher count of 35 microbubbles/mm 2 indicating good intra-observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…However, amniotic fluid collection at birth is difficult. As an index of the maturity of the fetal lung at birth, the microbubble test is commonly employed in Japan 3 . While some studies have investigated the SP‐A concentration in gastric fluid instead of amniotic fluid at birth, 4–7 there is no publication written in English, and cut‐off values vary due to limited data.…”
Section: There Were Significant Differences In the Birthweight And Gementioning
confidence: 99%
“…As an index of the maturity of the fetal lung at birth, the microbubble test is commonly employed in Japan. 3 While some studies have investigated the SP-A concentration in gastric fluid instead of amniotic fluid at birth, [4][5][6][7] there is no publication written in English, and cut-off values vary due to limited data. In this study, we performed a large-scale, retrospective analysis to examine the association between the gastric fluid concentration of SP-A and clinical symptoms in 179 neonates born in our hospital.…”
mentioning
confidence: 99%